Implementasi Metode Pembelajaran Bervariasi pada Materi SKI di Madrasah Ibtidaiyyah - Imelda Aprilia; Nelson Nelson; Sri Rahmaningsih; Idi Warsah (JIP Jurnal Ilmiah PGMI, 2020)
This study aimed at finding out the answers vis-a-vis the implementation of SKI learning by using varied methods towards the students of class V in MIM 10 of Karang Anyar, Curup, Bengkulu, through the application of a qualitative approach. In order to answer the questions as regards the implementation of such varied methods, some data collection techniques were deployed. Those techniques were observation, interviews, and documentation. After the data were obtained, the data were further processed, presented descriptively, and concluded. This study found a conclusion that the variations of learning methods used for the Islamic Culture History subject at class V in even semester included lecturing method, story-telling method, question and answer method, discussion method, drilling method (exercise), and recitation method (homework). The obstacles faced by SKI teachers in applying these varied methods extended to the lack of time allocation available for SKI learning, and the lack of facilities and infrastructure to support the application of the varied methods.